Composite dewatering agent for sludge dewatering in sewage treatment and preparation method thereof
Patent Information
- Application Number
- CN202610490575.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-04-14
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-04-14
AI Technical Summary
[0004]本发明提供一种用于污水处理中污泥脱水的复合型脱水剂及其制备方法,可以解决现有技术中存在的脱水剂脱水效果不佳的问题
(1)本发明的复合脱水剂包括壳聚糖-乙酰半胱氨酸修饰煤矸石、阳离子淀粉改性粉煤灰纤维和非离子表面活性剂,通过各组分的协同作用,在电荷中和作用、吸附架桥作用和胞外聚合物破坏释放结合水的多种机制下,大幅提高污泥的脱水率。
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sludge treatment technology, specifically relating to a composite dewatering agent for sludge dewatering in wastewater treatment and its preparation method. Background Technology
[0002] Wastewater treatment is a top priority in current environmental governance. A large amount of sludge is generated during the wastewater treatment process. The sludge produced after biochemical treatment generally has a water content between 95% and 99.5%, and is very large in volume, which is not conducive to transportation and disposal. Therefore, the sludge must be dewatered.
[0003] Water in sludge exists in four forms: free water, capillary-bound water, surface-adsorbed water, and internal water. Free water exists outside the sludge floc, does not interact with solid particles, and can be easily removed by mechanical dewatering. The other three forms, including capillary-bound water, surface-adsorbed water, and internal water, form complex physical and chemical interactions with sludge particles, collectively referred to as bound water, which is considered the main factor limiting sludge dewatering. Studies have shown that traditional dewatering agents (such as PAM and polyaluminum chloride) mainly improve dewatering performance through charge neutralization and flocculation, but they cannot effectively disrupt the extracellular polymeric substance (EPS) network structure where bound water resides. Therefore, their removal effect on bound water is not ideal, making it difficult to substantially improve sludge dewatering performance. Summary of the Invention
[0004] This invention provides a composite dewatering agent for sludge dewatering in wastewater treatment and its preparation method, which can solve the problem of poor dewatering effect of existing dewatering agents.
[0005] The objective of this invention can be achieved through the following technical solutions: A composite dewatering agent for sludge dewatering in wastewater treatment, comprising the following raw materials by weight: 30-50 parts of chitosan-acetylcysteine-modified coal gangue, 20-40 parts of cationic starch-modified fly ash fiber, and 1-3 parts of nonionic surfactant.
[0006] This invention utilizes solid waste as raw material for the dehydrating agent, using coal gangue and fly ash fiber as matrix materials. It modifies the material using natural polymeric flocculants, achieving valuable reuse of solid waste while reducing the secondary pollution hazards of the dehydrating agent. Using coal gangue as the matrix, modified chitosan, as a natural cationic flocculant, adsorbs negatively charged sludge particles through charge neutralization. Unlike simple chitosan flocculation and dehydration, the thiol groups in the surface-modified chitosan-acetylcysteine can disrupt the extracellular polymeric network structure, releasing bound water. Simultaneously, the thiol groups can chelate heavy metal ions, enhancing the solidification ability of heavy metals. Cationic starch-modified fly ash fiber differs from the particle structure of chitosan-acetylcysteine-modified coal gangue. Using fiber as the matrix, the cationic starch modification enhances the charge neutralization capacity, effectively flocculating gel particles. The fiber matrix structure is more conducive to the collision and bonding of cationic starch molecular chains with colloidal particles. Combined with the fiber's entanglement effect, it can form compact flocs. While chitosan-acetylcysteine-modified coal gangue and cationic starch-modified fly ash fiber promote the coagulation of sludge particles into flocs and their separation from water, nonionic surfactants can reduce surface tension and decrease water adsorption on the floc surface. The interwoven structure of particles and fibers constructed by chitosan-acetylcysteine-modified coal gangue and cationic starch-modified fly ash fiber is beneficial for water release during mechanical dewatering. The dewatering agent of this invention can efficiently improve the dewatering rate of sludge through the synergistic effect between materials.
[0007] Furthermore, the preparation steps of the chitosan-acetylcysteine modified coal gangue are as follows: A1. Mix coal gangue powder and calcium oxide, calcine at 650-700℃ for 1.5-2 hours, and grind to obtain activated coal gangue; A2. Prepare 3-aminopropyltriethoxysilane hydrolysate, add activated coal gangue, stir at room temperature for 8-12 hours, centrifuge, wash, and dry to obtain silane-modified coal gangue. A3. Prepare an aqueous solution of glutaraldehyde, add silane-modified coal gangue, stir at room temperature for 5-8 hours, centrifuge, wash, and dry to obtain the precursor. A4. Prepare a chitosan solution, add the precursor, and stir at room temperature for 3-4 hours to obtain a mixture. A5. Prepare an aqueous solution of acetylcysteine, add EDAC, adjust the pH of the solution to 4-5, stir and activate for 20-30 min to obtain an activated acetylcysteine solution. A6. Mix the activated acetylcysteine solution with the mixture, stir at room temperature for 3-5 hours, centrifuge, wash, freeze dry, and crush to obtain chitosan-acetylcysteine modified coal gangue.
[0008] After calcination, coal gangue mixed with calcium oxide develops a more loose and porous structure, enhancing its adsorption capacity. This process also generates more active silicon-oxygen and aluminum-oxygen bonds, providing reaction sites for subsequent modifications. Aminosilanes are used to introduce amino groups onto the surface of activated coal gangue. Glutaraldehyde is used as a crosslinking agent, reacting at one end with the amino groups on the silane-modified coal gangue surface and at the other end with the amino groups on the chitosan molecular chains, thus binding the chitosan molecular chains to the coal gangue surface. EDAC activates the carboxyl groups of acetylcysteine, causing them to react with the amino groups on the chitosan molecular chains to form amide bonds. Thiol groups are then introduced onto the side chains of the chitosan molecular chains, resulting in chitosan-acetylcysteine-modified coal gangue.
[0009] Furthermore, the mass ratio of the coal gangue powder to calcium oxide is 4-6:1.
[0010] Furthermore, in the 3-aminopropyltriethoxysilane hydrolysate, the ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.0mL-1.5mL:90mL:10mL; The mass ratio of the activated coal gangue to the 3-aminopropyltriethoxysilane hydrolysate is 2-5:100.
[0011] Furthermore, the glutaraldehyde aqueous solution contains 1-2 wt% glutaraldehyde. The ratio of the silane-modified coal gangue to the glutaraldehyde aqueous solution is 3-8g:250mL.
[0012] Furthermore, the chitosan concentration of the chitosan solution is 1-1.5 wt%; The ratio of the precursor to the chitosan solution is 2-6 g: 100 mL.
[0013] Furthermore, the acetylcysteine concentration in the aqueous acetylcysteine solution is 5-9 wt%. The mass ratio of EDAC to acetylcysteine is 0.2-0.6:1.
[0014] Furthermore, the activated acetylcysteine solution and the mixture are mixed at a mass ratio of acetylcysteine to chitosan of 0.2-0.4:1.
[0015] Furthermore, the preparation steps of the cationic starch-modified fly ash fiber are as follows: B1. Immerse fly ash fibers in hydrochloric acid solution for 20-40 minutes, filter, wash, and dry to obtain acid-treated fly ash fibers; B2. Prepare a cationic starch aqueous solution, add acid-treated fly ash fiber, stir and react at 30-50℃ for 20-60 min, filter, wash and dry to obtain cationic starch modified fly ash fiber.
[0016] The surface of fly ash fibers treated with hydrochloric acid is roughened, and active hydroxyl groups are introduced. The positive charge on the cationic starch can combine with the negative charge on the surface of the acid-treated fly ash through electrostatic adsorption and hydrogen bonding, thus realizing the cationic starch-modified fly ash fiber. The fiber surface is positively charged after cationic modification, which can effectively exert charge neutralization and flocculation capabilities.
[0017] Furthermore, the concentration of the hydrochloric acid solution is 0.2-0.3 mol / L.
[0018] Furthermore, the cationic starch concentration in the cationic starch aqueous solution is 0.05-0.20 wt%.
[0019] Furthermore, the mass ratio of the acid-treated fly ash fiber to the cationic starch in the cationic starch aqueous solution is 30-100:1.
[0020] Furthermore, the nonionic surfactant is an alkyl glycoside. Alkyl glycosides (APGs) are synthesized from natural fatty alcohols and glucose and have extremely low surface tension.
[0021] This invention also provides a method for preparing a composite dewatering agent for sludge dewatering in wastewater treatment, comprising the following steps: Prepare raw materials according to the proportions, stir and mix chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber and nonionic surfactant, and dry to obtain a composite dehydrating agent.
[0022] The beneficial effects of this invention are: (1) The composite dewatering agent of the present invention includes chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber and nonionic surfactant. Through the synergistic effect of each component, the dewatering rate of sludge is greatly improved through multiple mechanisms such as charge neutralization, adsorption bridging and extracellular polymer destruction to release bound water.
[0023] (2) This invention makes full use of solid waste and natural materials, realizing the resource utilization of solid waste while avoiding the residual pollution of traditional polyacrylamide flocculants and reducing environmental hazards.
[0024] (3) Chitosan-acetylcysteine-modified coal gangue and cationic starch-modified fly ash fibers contain chitosan and cationic starch with high molecular weight long chain structures. Under the action of active groups (such as amino and quaternary ammonium groups), multiple sludge particles can be captured and adsorbed simultaneously to form flocs, which facilitates the subsequent separation of sludge and water. In mechanical dewatering, the supporting structure built by coal gangue and fibers can provide a channel for water to be discharged in the sludge flocs, which facilitates drainage and reduces the moisture content of the sludge cake after mechanical dewatering. The thiol groups on the surface of chitosan-acetylcysteine-modified coal gangue can break the disulfide bonds in the protein structure, making the protein structure loose and destroying the tight network structure of the extracellular polymer, releasing bound water.
[0025] (4) The thiol group of chitosan-acetylcysteine-modified coal gangue has a strong coordination effect on heavy metal ions, which can form a stable complex, thereby solidifying the heavy metals. In synergy with the metal chelation effect of chitosan, the metal ions in the sludge are fixed in the sludge, preventing secondary pollution in the dewatering filtrate. Detailed Implementation
[0026] The specific embodiments of the present invention will be described in detail below, but it should be understood that the scope of protection of the present invention is not limited to the specific embodiments.
[0027] Example 1 Preparation of chitosan-acetylcysteine modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0028] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0029] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0030] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a chitosan solution with a chitosan concentration of 1.2 wt%. Add the precursor, with a ratio of 4 g to 100 mL of precursor to chitosan solution. Stir at room temperature for 3.5 h to obtain a mixed solution.
[0031] A5. Prepare an aqueous solution of acetylcysteine with a concentration of 7 wt%, add EDAC (e.g., EDAC to acetylcysteine in a mass ratio of 0.4:1), adjust the pH of the solution to 4.5, and stir for 20 min to obtain an activated acetylcysteine solution.
[0032] A6. The activated acetylcysteine solution was mixed with the mixture at a mass ratio of 0.3:1 for acetylcysteine and chitosan. The mixture was stirred at room temperature for 4 hours, centrifuged, washed, freeze-dried, and crushed to obtain chitosan-acetylcysteine modified coal gangue.
[0033] Preparation of cationic starch-modified fly ash fibers: B1. Prepare a hydrochloric acid solution with a concentration of 0.2 mol / L, immerse the fly ash fiber in the hydrochloric acid solution for 30 min, filter, wash, and dry to obtain acid-treated fly ash fiber.
[0034] B2. Add cationic starch to cold water and stir. Heat to 95℃ and keep warm for 20 minutes to obtain a paste-like liquid. Add deionized water and stir for 30 minutes to obtain a cationic starch aqueous solution with a cationic starch concentration of 0.1 wt%. Add acid-treated fly ash fiber with a mass ratio of acid-treated fly ash fiber to cationic starch in the cationic starch aqueous solution of 60:1. Stir and react at 40℃ for 40 minutes. Filter, wash, and dry to obtain cationic starch modified fly ash fiber.
[0035] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0036] Example 2 The only difference from Example 1 is that the chitosan concentration was adjusted to 1.5 wt% when preparing chitosan-acetylcysteine modified coal gangue.
[0037] Preparation of chitosan-acetylcysteine modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0038] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0039] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0040] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a 1.5 wt% chitosan solution, add the precursor, the ratio of precursor to chitosan solution is 4 g: 100 mL, stir at room temperature for 3.5 h to obtain a mixture.
[0041] A5. Prepare an aqueous solution of acetylcysteine with a concentration of 7 wt%, add EDAC (e.g., EDAC to acetylcysteine in a mass ratio of 0.4:1), adjust the pH of the solution to 4.5, and stir for 20 min to obtain an activated acetylcysteine solution.
[0042] A6. The activated acetylcysteine solution was mixed with the mixture at a mass ratio of 0.3:1 for acetylcysteine and chitosan. The mixture was stirred at room temperature for 4 hours, centrifuged, washed, freeze-dried, and crushed to obtain chitosan-acetylcysteine modified coal gangue.
[0043] The conditions and steps for preparing cationic starch-modified fly ash fibers are the same as in Example 1.
[0044] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0045] Example 3 The only difference from Example 1 is that the chitosan concentration was adjusted to 1.0 wt% when preparing chitosan-acetylcysteine modified coal gangue.
[0046] Preparation of chitosan-acetylcysteine modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0047] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0048] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0049] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a chitosan solution with a chitosan concentration of 1.0 wt%. Add the precursor, with a ratio of 4 g to 100 mL of precursor to chitosan solution. Stir at room temperature for 3.5 h to obtain a mixed solution.
[0050] A5. Prepare an aqueous solution of acetylcysteine with a concentration of 7 wt%, add EDAC (e.g., EDAC to acetylcysteine in a mass ratio of 0.4:1), adjust the pH of the solution to 4.5, and stir for 20 min to obtain an activated acetylcysteine solution.
[0051] A6. The activated acetylcysteine solution was mixed with the mixture at a mass ratio of 0.3:1 for acetylcysteine and chitosan. The mixture was stirred at room temperature for 4 hours, centrifuged, washed, freeze-dried, and crushed to obtain chitosan-acetylcysteine modified coal gangue.
[0052] The conditions and steps for preparing cationic starch-modified fly ash fibers are the same as in Example 1.
[0053] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0054] Example 4 The only difference from Example 1 is that, in preparing chitosan-acetylcysteine modified coal gangue, the activated acetylcysteine solution is mixed with the mixture at a mass ratio of acetylcysteine to chitosan of 0.4:1.
[0055] Preparation of chitosan-acetylcysteine modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0056] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0057] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0058] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a chitosan solution with a chitosan concentration of 1.2 wt%. Add the precursor, with a ratio of 4 g to 100 mL of precursor to chitosan solution. Stir at room temperature for 3.5 h to obtain a mixed solution.
[0059] A5. Prepare an aqueous solution of acetylcysteine with a concentration of 7 wt%, add EDAC (e.g., EDAC to acetylcysteine in a mass ratio of 0.4:1), adjust the pH of the solution to 4.5, and stir for 20 min to obtain an activated acetylcysteine solution.
[0060] A6. The activated acetylcysteine solution was mixed with the mixture at a mass ratio of 0.4:1 for acetylcysteine and chitosan. The mixture was stirred at room temperature for 4 hours, centrifuged, washed, freeze-dried, and crushed to obtain chitosan-acetylcysteine modified coal gangue.
[0061] The conditions and steps for preparing cationic starch-modified fly ash fibers are the same as in Example 1.
[0062] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0063] Example 5 The only difference from Example 1 is that, in preparing chitosan-acetylcysteine modified coal gangue, the activated acetylcysteine solution is mixed with the mixture at a mass ratio of acetylcysteine to chitosan of 0.2:1.
[0064] Preparation of chitosan-acetylcysteine modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0065] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0066] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0067] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a chitosan solution with a chitosan concentration of 1.2 wt%. Add the precursor, with a ratio of 4 g to 100 mL of precursor to chitosan solution. Stir at room temperature for 3.5 h to obtain a mixed solution.
[0068] A5. Prepare an aqueous solution of acetylcysteine with a concentration of 7 wt%, add EDAC (e.g., EDAC to acetylcysteine in a mass ratio of 0.4:1), adjust the pH of the solution to 4.5, and stir for 20 min to obtain an activated acetylcysteine solution.
[0069] A6. The activated acetylcysteine solution was mixed with the mixture at a mass ratio of 0.2:1 for acetylcysteine and chitosan. The mixture was stirred at room temperature for 4 hours, centrifuged, washed, freeze-dried, and crushed to obtain chitosan-acetylcysteine modified coal gangue.
[0070] The conditions and steps for preparing cationic starch-modified fly ash fibers are the same as in Example 1.
[0071] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0072] Example 6 The only difference from Example 1 is that, in preparing cationic starch modified fly ash fiber, the mass ratio of acid-treated fly ash fiber to cationic starch in the cationic starch aqueous solution is 30:1.
[0073] The conditions and steps for preparing chitosan-acetylcysteine-modified coal gangue are the same as in Example 1.
[0074] Preparation of cationic starch-modified fly ash fibers: B1. Prepare a hydrochloric acid solution with a concentration of 0.2 mol / L, immerse the fly ash fiber in the hydrochloric acid solution for 30 min, filter, wash, and dry to obtain acid-treated fly ash fiber.
[0075] B2. Add cationic starch to cold water and stir. Heat to 95℃ and keep warm for 20 minutes to obtain a paste-like liquid. Add deionized water and stir for 30 minutes to obtain a cationic starch aqueous solution with a cationic starch concentration of 0.1 wt%. Add acid-treated fly ash fiber with a mass ratio of acid-treated fly ash fiber to cationic starch in the cationic starch aqueous solution of 30:1. Stir and react at 40℃ for 40 minutes. Filter, wash, and dry to obtain cationic starch modified fly ash fiber.
[0076] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0077] Example 7 The only difference from Example 1 is that, in preparing cationic starch modified fly ash fiber, the mass ratio of acid-treated fly ash fiber to cationic starch in the cationic starch aqueous solution is 100:1.
[0078] The conditions and steps for preparing chitosan-acetylcysteine-modified coal gangue are the same as in Example 1.
[0079] Preparation of cationic starch-modified fly ash fibers: B1. Prepare a hydrochloric acid solution with a concentration of 0.2 mol / L, immerse the fly ash fiber in the hydrochloric acid solution for 30 min, filter, wash, and dry to obtain acid-treated fly ash fiber.
[0080] B2. Add cationic starch to cold water and stir. Heat to 95℃ and keep warm for 20 minutes to obtain a paste-like liquid. Add deionized water and stir for 30 minutes to obtain a cationic starch aqueous solution with a cationic starch concentration of 0.1 wt%. Add acid-treated fly ash fiber with a mass ratio of acid-treated fly ash fiber to cationic starch in the cationic starch aqueous solution of 100:1. Stir and react at 40℃ for 40 minutes. Filter, wash, and dry to obtain cationic starch modified fly ash fiber.
[0081] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0082] Examples 8-9 The only difference from Example 1 is that the proportion of raw materials in the composite dehydrating agent is different, and the specific proportions are shown in Table 1.
[0083] Table 1
[0084] Comparative Example 1 The only difference from Example 1 is that chitosan-modified coal gangue is used instead of chitosan-acetylcysteine-modified coal gangue.
[0085] Preparation of chitosan-modified coal gangue: A1. Weigh coal gangue powder and calcium oxide at a mass ratio of 5:1, stir and mix, place in a muffle furnace and calcine at 700℃ for 1.5h, grind and sieve through a 100-mesh sieve to obtain activated coal gangue.
[0086] A2. Prepare an ethanol-water solution at a volume ratio of 9:1 (ethanol to water). Measure 3-aminopropyltriethoxysilane and add it to the ethanol-water solution. The ratio of 3-aminopropyltriethoxysilane:ethanol:water is 1.4 mL:90 mL:10 mL. After hydrolysis for 30 min, obtain the hydrolysate. Add activated coal gangue at a mass ratio of 4:100 (activated coal gangue to 3-aminopropyltriethoxysilane hydrolysate). Stir the reaction at room temperature for 10 h, then centrifuge, wash, and dry to obtain silane-modified coal gangue.
[0087] A3. Prepare an aqueous solution of glutaraldehyde with a mass fraction of 1.5%, add silane-modified coal gangue, and add silane-modified coal gangue to glutaraldehyde aqueous solution in a ratio of 5g:250mL. Stir the reaction at room temperature for 6h, then centrifuge, wash, and dry to obtain the precursor.
[0088] A4. Prepare a 1 wt% acetic acid solution, add chitosan and stir to dissolve to obtain a chitosan solution with a chitosan concentration of 1.2 wt%. Add the precursor, with a precursor to chitosan solution ratio of 4 g: 100 mL. Stir at room temperature for 7.5 h, centrifuge, wash, freeze dry, and crush to obtain chitosan-acetylcysteine modified coal gangue.
[0089] The conditions and steps for preparing cationic starch-modified fly ash fibers are the same as in Example 1.
[0090] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue, 30 parts by mass of cationic starch modified fly ash fiber, and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber, and alkyl glycoside, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0091] Comparative Example 2 The only difference from Example 1 is that cationic starch-modified fly ash fiber is not added.
[0092] The conditions and steps for preparing chitosan-acetylcysteine-modified coal gangue and cationic starch-modified fly ash fibers are the same as in Example 1.
[0093] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue and 2 parts by mass of alkyl glycoside. Mix the chitosan-acetylcysteine modified coal gangue and alkyl glycoside, and dry at 60℃ for 120 min to obtain a composite dehydrating agent.
[0094] Comparative Example 3 The only difference from Example 1 is that no alkyl glycosides are added.
[0095] The conditions and steps for preparing chitosan-acetylcysteine-modified coal gangue and cationic starch-modified fly ash fibers are the same as in Example 1.
[0096] A composite dewatering agent for sludge dewatering in wastewater treatment, the specific preparation steps are as follows: Prepare 40 parts by mass of chitosan-acetylcysteine modified coal gangue and 30 parts by mass of cationic starch modified fly ash fiber. Mix the chitosan-acetylcysteine modified coal gangue and cationic starch modified fly ash fiber, and dry them at 60℃ for 120 min to obtain a composite dehydrating agent.
[0097] Comparative Example 4 The only difference from Example 1 is that polyacrylamide is used as the dehydrating agent.
[0098] The sludge dewatering performance of the dewatering agents obtained in Examples 1-9 and Comparative Examples 1-4 was tested, and the results are shown in Table 2.
[0099] Take 100g of sludge with a moisture content of 97.28% and a pH of 6.7. Add the dewatering agent to the sludge at a concentration of 1% of the sludge mass. Stir at 200r / min for 20min. Dewater using a sludge resistivity meter to measure the sludge resistivity and the moisture content of the sludge cake. Set the filtration pressure to 0.6MPa and the dewatering time to 20min.
[0100] Table 2
[0101] As can be seen from Table 2, the dewatering agent in the embodiments of the present invention can significantly improve the dewatering rate of sludge, and the moisture content of the sludge cake obtained after treatment can be as low as 53.43%, demonstrating excellent dewatering effect.
[0102] The above-disclosed embodiments are merely a few specific examples of the present invention. However, the embodiments of the present invention are not limited thereto, and any variations that can be conceived by those skilled in the art should fall within the protection scope of the present invention.
Claims
1. A composite dewatering agent for sludge dewatering in wastewater treatment, characterized in that, By weight, it includes the following raw materials: 30-50 parts of chitosan-acetylcysteine-modified coal gangue, 20-40 parts of cationic starch-modified fly ash fiber, and 1-3 parts of nonionic surfactant; The preparation steps of the chitosan-acetylcysteine modified coal gangue are as follows: A1. Mix coal gangue powder and calcium oxide, calcine at 650-700℃ for 1.5-2 hours, and grind to obtain activated coal gangue; A2. Prepare 3-aminopropyltriethoxysilane hydrolysate, add activated coal gangue, stir at room temperature for 8-12 hours, centrifuge, wash, and dry to obtain silane-modified coal gangue. A3. Prepare an aqueous solution of glutaraldehyde, add silane-modified coal gangue, stir at room temperature for 5-8 hours, centrifuge, wash, and dry to obtain the precursor. A4. Prepare a chitosan solution, add the precursor, and stir at room temperature for 3-4 hours to obtain a mixture. A5. Prepare an aqueous solution of acetylcysteine, add EDAC, adjust the pH of the solution to 4-5, stir and activate for 20-30 min to obtain an activated acetylcysteine solution. A6. Mix the activated acetylcysteine solution with the mixture, stir at room temperature for 3-5 hours, centrifuge, wash, freeze dry, and crush to obtain chitosan-acetylcysteine modified coal gangue; The preparation steps of the cationic starch modified fly ash fiber are as follows: B1. Immerse fly ash fibers in hydrochloric acid solution for 20-40 minutes, filter, wash, and dry to obtain acid-treated fly ash fibers; B2. Prepare a cationic starch aqueous solution, add acid-treated fly ash fiber, stir and react at 30-50℃ for 20-60 min, filter, wash and dry to obtain cationic starch modified fly ash fiber.
2. The composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The hydrolysate of 3-aminopropyltriethoxysilane contains 3-aminopropyltriethoxysilane:ethanol:water in a ratio of 1.0 mL to 1.5 mL:90 mL:10 mL. The mass ratio of the activated coal gangue to the 3-aminopropyltriethoxysilane hydrolysate is 2-5:
100.
3. The composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The glutaraldehyde aqueous solution has a glutaraldehyde mass fraction of 1-2 wt%. The ratio of the silane-modified coal gangue to the glutaraldehyde aqueous solution is 3-8g:250mL.
4. A composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The chitosan concentration of the chitosan solution is 1-1.5 wt%. The ratio of the precursor to the chitosan solution is 2-6 g: 100 mL.
5. A composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The acetylcysteine concentration in the aqueous solution is 5-9 wt%. The mass ratio of EDAC to acetylcysteine is 0.2-0.6:
1.
6. A composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The activated acetylcysteine solution and the mixture are mixed at a mass ratio of acetylcysteine to chitosan of 0.2-0.4:
1.
7. A composite dewatering agent for sludge dewatering in wastewater treatment according to claim 1, characterized in that, The concentration of the hydrochloric acid solution is 0.2-0.3 mol / L; The cationic starch concentration in the cationic starch aqueous solution is 0.05-0.20 wt%. The mass ratio of the acid-treated fly ash fiber to the cationic starch in the cationic starch aqueous solution is 30-100:
1.
8. A method for preparing a composite dewatering agent for sludge dewatering in wastewater treatment, characterized in that, The preparation of the composite dewatering agent for sludge dewatering in wastewater treatment as described in any one of claims 1-7 comprises the following steps: Prepare raw materials according to the proportions, stir and mix chitosan-acetylcysteine modified coal gangue, cationic starch modified fly ash fiber and nonionic surfactant, and dry to obtain a composite dehydrating agent.
Citation Information
Patent Citations
Surface cationization modifying method for inorganic fiber applied to papermaking
CN102454127A
Biochar adsorbent based on ball milling modification as well as preparation method and application thereof
CN120532449A
